Pengaruh Tingkat Bunga Terhadap Biaya - Widana, I Nyoman (Jurnal Matematika; Vol 1 No 2 (2011), 2012)
This article discusses the impact of interest rates on expense rates. An insurance expense is the difference calculated between Gross Premium and Net Premium. The calculations indicate that the expense reduces when the interest rate increases.
Keywords: Gross Premium, Net Premium, interest rate, expenses rate